Analysis of the interaction of ACE2, TMPRSS2 genes and their polymorphisms with the SARS-CoV-2 virus - Bisseneva А.K.; Pogossyan, G.P.; Li, K.G.; Danilenko, M.P. (Fundamental and Experimental Biology, 2022)
Host genes act as a factor related to susceptibility and resistance to viral infections. The article provides a description of modern scientific studies devoted to the study of the role of the ACE2, TMPRSS2 genes, and their single-nucleotide polymorphisms in infection with the SARS-CoV-2virus. SNPs of the ACE2 gene, TMPRSS2 can affect the penetration of SARS-CoV-2 into the cell. In addition, the study of these polymor-phisms will determine the predisposition of an individual to the disease COVID–19, or the nature of its course. Based on the literature sources, the role of angiotensin-converting enzyme 2 and transmembrane proteases in the participation of the SARS-CoV-2 virus penetration process with the body cells is noted. Other functions that ACE2 and TMPRSS2 receptors perform in the human body are also described. The characteristics of two genes and their fairly well-known polymorphisms are given. The tissues and organs in which genes are expressed are marked. Information on the frequency of alleles of genetic variants of genes in different populations is shown. In addition to describing the relationship of gene polymorphisms with the disease caused by SARS-CoV-2, information is provided on the association of these genetic variations with diseases of the blood vascular system and oncological diseases.